Support for Palestine Among Indonesian Muslims: Religious Identityand Solidarity as Reasons for E-PetitionSigning - Shadiqi, Muhammad Abdan; Muluk, Hamdi; Milla, Mirra Noor (Psychological Research on Urban Society, 2020)
A petition is a form of collective action urging the government or a public entity to resolve a specific situation. There is inconsistency between previous research on whether religious or political identity is more likely to lead to radical or peaceful actions, especially in terms of how feelings of solidarity relate to religious-political issues. This study examines the reasons Indonesians signed e-petitions supporting Palestine. Data were collected from the comment sections of e-petitions supporting Palestine on change.org. In total, we analyzed 380 comments from 25 e-petitions using a qualitative approach. Using NVivo for thematic analysis, we found that the most recurring themes were moral violation, followed by independence for Palestine, solidarity, hatred as a negative emotion, and religious identity. Additionally, matrix nodes analysis showed identification with Islam was related to solidarity. These findings suggest that the similarity of religious identity in the two nations can be associated with solidarity as a reason for signing the e-petitions. We also discussed the association between moral violation and independence for Palestine as reasons for signing the e-petitions.